2016
DOI: 10.1108/bfj-03-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

The role of intermediaries in food export: case evidence from Finland

Abstract: Purpose This paper examines the role of export intermediaries in the internationalization of small and medium sized companies in Finland. The empirical study focuses on small Finnish food companies that export to German and Chinese markets. Design/methodology/approach The research method of this study is qualitative. Data is collected through semi-structured interviews with six respondents presenting exporting companies and export consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 36 publications
(45 reference statements)
3
34
0
Order By: Relevance
“…Similarly, H7 was supported; the finding shown that trust has a significantly positive relationship with export performance in the context of exporter and intermediary. The result is in tandem with previous studies which have noted that trust significantly contributes to competitiveness in foreign markets (e.g., Lehtinen et al, 2016;Hador, 2017). Also, the presence of trust is seen as being able to lower transaction costs and improve investment in relationship-specific assets and superior information sharing routines (Dyer & Chu, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, H7 was supported; the finding shown that trust has a significantly positive relationship with export performance in the context of exporter and intermediary. The result is in tandem with previous studies which have noted that trust significantly contributes to competitiveness in foreign markets (e.g., Lehtinen et al, 2016;Hador, 2017). Also, the presence of trust is seen as being able to lower transaction costs and improve investment in relationship-specific assets and superior information sharing routines (Dyer & Chu, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The challenging issues for countries are to strengthen the determinants of the duration of comparative advantages as well as to transform disadvantages into advantages in international trade (e.g., Curzi and Olper, 2012). To achieve comparative advantages, countries and firms can use different export strategies (e.g., Ritthaisong et al, 2014;Lehtinen et al, 2016). Following the previous research on the duration of trade and comparative advantage we set the following hypotheses.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A body of literature has been developed about resource determinants of export performance across industries and countries (e.g., Beleska-Spasova et al, 2012;Lehtinen et al, 2016). A large part of agricultural production depends on endowments with natural agricultural resources (e.g., Anderson 1998;Huo 2014).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The study of export performance attracted attention in early literature (Aulakh, Rotate, & Teegen, 2000;Kedia & Chhokar, 1986). In the food domain, a number of studies have focused on small and medium-sized enterprises from various sectors (Casey & Hamilton, 2014;Freeman, Styles, & Lawley, 2012;Maldifassi & Chacón Caorsi, 2014;Zeriti, Robson, Spyropoulou, & Leonidou, 2014), while others have focused solely on export performance related to certain food products (Alteren & Tudoran, 2016;Galdeano-Gómez, Pérez-Mesa, & Giagnocavo, 2015;Karelakis, Mattas, & Chryssochoidis, 2008;Lehtinen, Ahokangas, & Lu, 2016;Maurel, 2009;Mavrogiannis, Bourlakis, Dawson, & Ness, 2008).…”
Section: Export Performance Of Food Firmsmentioning
confidence: 99%